The Differences Between Interleukin-6 and C-reactive Protein Levels Among Adult Patients of Dengue Infection with and without Plasma Leakage - Eppy Eppy; Suhendro Suhendro; Leonard Nainggolan; Cleopas M Rumende (Interna Publishing, 2016)
Aim: to determine the differences in IL-6 and CRP levels among groups of dengue infection patients with and without plasma leakage. Methods:a cross-sectional study was conducted in adult patients with dengue infection who were treated at Cipto Mangunkusumo and Persahabatan Hospital between 1 March 2014 and 1 April 2015. The study analyzed differences in IL-6 and CRP levels on the 3rd and 5th day of fever in both groups, as well as differences in each group. Interleukin-6 and CRP levels in both groups, was analyzed using unpaired t-test or MannWhitney and in each group, the data was subsequently analyzed using paired t-test or Wilcoxon test. Results: the samples of study consisted of 24 subjects with plasma leakage and 20 subjects without plasma leakage. The level of IL-6 for groups with and without plasma leakage for the 3rd and the 5th day of fever were 8.56 (1.85-96.15) vs. 3.80 (1.94-81.93) pg/mL (p=0.069) and 4.30 (1.60-70.28) vs. 2.76 (1.26-11.67) pg/mL (p=0.025), respectively; while for CRP level, there were 10.1 (4.3-36.5) vs 6.8 (3.0-21.6) mg/L (p=0.014) and 5.0 (2.0-20.1) vs 2.9 (0.1-9.9) mg/L (p=0.048). The level of IL-6 on the 3rd and the 5th day of fever in the group with and without plasma leakage were 8.56 (1.85-96.15) vs. 4.30 (1.60-70.28) pg/mL (p=0.037) and 3.80 (1.94-81.93) vs. 2.76 (1.26-11.67) pg/mL (p=0.005). The level of CRP on the 3rd and 5th day of fever in the group with and without plasma leakage were 10.1 (4.3-36.5) vs. 5.0 (2.0-20.1) mg/L (p=0.0001) and 6.8 (0.3-21.6) vs. 2.9 (0.1-9.9) mg/L (p=0.0001). Conclusion:there was no difference in IL-6 level on the 3rd day of fever between the two groups; while on the 5th day of fever, the IL-6 level was higher in the group with plasma leakage. The level of CRP on the 3rd and the 5th day of fever were higher in the group with plasma leakage. The levels of IL-6 and CRP on the 3rd day of fever were higher than the levels on the 5th day of fever in both groups.